2019
DOI: 10.1186/s11671-019-3108-6
|View full text |Cite|
|
Sign up to set email alerts
|

Polymer Microfibers Incorporated with Silver Nanoparticles: a New Platform for Optical Sensing

Abstract: The enhanced sensitivity of up-conversion luminescence is imperative for the application of up-conversion nanoparticles (UCNPs). In this study, microfibers were fabricated after co-doping UCNPs with polymethylmethacrylate (PMMA) and silver (Ag) solutions. Transmission losses and sensitivities of UCNPs (tetrogonal-LiYF 4 :Yb 3+ /Er 3+ ) in the presence and absence of Ag were investigated. Sensitivity of up-conversion luminescence with Ag (LiYF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Moreover, higher the values of the thread setting density, linear density, weight per square meter (GSM), and tensile properties better will be the performance and quality of textile products [38,39]. The recycled textile and composites materials have reasonable applications in optical sensing, automobiles and medical industries [40,41]. Based on literature and experimental results, it can be concluded that relative sliding COF value between textile waste and metallic components during shredding, cutting, and recycling should be greater than 0.25 due to damage, rough, and the distorted surface of textile fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, higher the values of the thread setting density, linear density, weight per square meter (GSM), and tensile properties better will be the performance and quality of textile products [38,39]. The recycled textile and composites materials have reasonable applications in optical sensing, automobiles and medical industries [40,41]. Based on literature and experimental results, it can be concluded that relative sliding COF value between textile waste and metallic components during shredding, cutting, and recycling should be greater than 0.25 due to damage, rough, and the distorted surface of textile fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 10G, the scattering intensity of the GNR decreased monotonically with increasing RH, offering a sensitivity of $0.07 dB/% RH and an estimated resolution better than 1% RH (Wang et al, 2012a). Recently, more functional materials, such as proteins (Sun et al, 2015), ZnO nanostructures (Irawati et al, 2017a), CdSe quantum dot (Irawati et al, 2017b), silver nanoparticles (Shahzad et al, 2019), and molecular imprinted nanoparticles (Shrivastav et al, 2019) have been incorporated with MNFs for optical sensing.…”
Section: Hybrid Mnf Structures For Advanced Optical Sensing Functionalized Polymer Mnf Sensorsmentioning
confidence: 99%
“…1 Hyperthermia therapies are commonly used in combination with other cancer treatments such as chemotherapy or radiation therapy because heat-stressed cells are more responsive to treatment. 2,3 This method of treatment uses external physical methods to increase the temperature of the tumor region between 42 C to 48 C. An increase in temperature can be localized or systemic, affecting the entire body and its treatment strategy. Hyperthermia consists of three types, local hyperthermia, regional hyperthermia, and whole-body hyperthermia.…”
Section: Introductionmentioning
confidence: 99%